A TRANSECT IN SOUTHERN TUSCANY, FROM THE BACCINELLO BASIN TO THE CETONA RIDGE - Sani, Federico; Moratti, Giovanna; Bonini, Marco; Landi, Barbara; Tanini, Chiara; Piccardi, Luigi; Menichetti, Barbara (Ofioliti, 2007)
The Northern Apennines (NA) is a NE-verging thrust and fold belt (Fig. 1) produced by the Cenozoic collision between the Corso-Sardinian block and the Adria Plate (Boccaletti and Guazzone, 1972; 1974; Principi and Treves, 1984; Malinverno and Ryan, 1986, among others). The NA thrust-nappe pile consists of sequences deposited on the Adria Plate continental margin (Tuscan and Umbria-Marche Units) which were overthrust by the Ligurian Units during continental collision. The Ligurian Units, which consist of ophiolites and their sedimentary covers, represent the remnants of the Ligurian-Piedmont paleo-ocean (Abbate et al., 1970). The NA evolution, after the Oligocene continental collisional phase, has been referred to two different models. In the first one, the development of an external thrust belt shifting eastwards, coupled with an internal extensional area is envisaged. In this process both the crust and the lithosphere would be involved (Merla, 1951; Boccaletti and Guazzone, 1974; Elter et al., 1975; Carmignani et al., 1980; Boccaletti et al., 1990; Patacca et al., 1990). In front of the migrating chain a foredeep basin developed during Late Oligocene-Miocene, whose deposits were progressively annexed to the chain (Ricci Lucchi, 1986; Boccaletti et al., 1990). In the second model, the accretionary prism, thickened by crustal collision, would collapse to recover its equilibrium conditions (Carmignani and Kligfield, 1990). As a consequence of the gravitational collapse, the development of core complex structures and of extensional tectonics has taken place since Burdigalian-Langhian (Carmignani et al., 1994). In this model, the Northern Apennines thrust belt is explained as due to gravitational tectonics active since the Early Miocene (Decandia et al., 1993; Carmignani et al., 1995). Starting in late Tortonian, the internal area (hinterland) of NA was characterized by the development of continental and marine basins, mostly striking from NW-SE to N-S, and subparallel to the main thrust fronts of the chain. Their formation has been commonly referred to the extensional processes related to the opening of the Tyrrhenian Basin, either in a back-arc regime (Boccaletti and Guazzone, 1972; 1974; Malinverno and Ryan, 1986; Royden et al., 1987; Boccaletti et al., 1990; Patacca et al., 1990), or as due to late orogenic gravity collapse (Carmignani and Kligfield, 1990; Cameli et al., 1993; Carmignani et al., 1994; Keller et al., 1994). The eastward younging trend of the hinterland basins has been related to the eastward shifting of the extensional front, which followed the migration of the thrust front (Merla 1951; Elter et al., 1975). However, in the last two decades structural studies have shown that the deposits of the hinterland basins have been affected by widespread compressional deformations and by major angular unconformities (Boccaletti et al., 1995, and references therein) that allow to subdivide the entire succession into five Unconformity Bounded Stratigraphic Units (UBSUs, Salvador, 1987).) since the unconformities that limited each UBSU have been correlated on a regional scale, (Boccaletti et al., 1994; 1995). The deformations affecting the basin fill, their architecture, the presence of regional unconformities strongly suggest that they have mostly developed under a compressional tectonic regime, tied to reactivation of thrust faults affecting the pre-Neogene substrate (Boccaletti et al., 1995; 1997; Bonini and Moratti, 1995; Landi et al., 1995). The objective of this excursion, whose road log is reported in Fig. 2, is to illustrate the relationships between tectonics and sedimentation in the hinterland basins along a transect across Southern Tuscany including the Baccinello-Cinigiano, Velona and Siena-Radicofani Basins. In this area, basin development has been mainly related to the activity of two crustal thrusts: the Mid-Tuscany Metamorphic Ridge and the Cetona Mountain thrusts (Fig. 3).